Dārajiliṅgera itihāsa - Śānyāla, Harimohana; Sarakāra, Ichāmuddīna. (Kalakātā : Mitraṃ, 2005)
History of Darjeeling District, India in the late 19th century.
In Bengali.
Originally published: 1880.
Includes bibliographical references.
committed to retain
Keywords: Darjeeling (India : District) -- History; India -- Darjeeling (District); History